Analisis Elemen Hingga Berbasis Elemen Fiber Penampang Pada Kolom Beton Bertulang - Mahmud Kori Effendi (Universitas Syiah Kuala, 2026)
Reinforced concrete structures are among the most widely used construction types in Indonesia and have been proven to possess good resistance against seismic loads, particularly through the implementation of the Strong Column–Weak Beam (SCWB) concept, which requires column capacity to exceed that of beams. Concentrically loaded columns, which carry pure axial loads without bending moments due to eccentricity, play a crucial role in ensuring ductile structural behavior. Previous studies have shown that the compressive capacity of columns is influenced by the longitudinal reinforcement ratio, stirrup spacing and configuration, as well as cross-sectional shape. Closer confinement spacing can enhance compressive capacity, while variations in cross-sectional shape yield different structural responses. In this study, a finite element method based on the fiber element approach is employed to analyze the behavior of reinforced concrete columns under concentric axial loading. This method models the cross-section as uniaxial elastic–plastic fibers to capture nonlinear behavior in detail. The load–deflection curves from the fiber element analysis exhibit a trend closely matching the experimental results. Concrete stresses reached ultimate levels, while steel tensile/compressive stresses reached yield at mid-span of the column. The ultimate load values from both the analysis and experiments were greater than those prescribed by SNI 2847:2019.